A influência da varanda no aproveitamento da iluminação natural na arquitetura residencial vertical no trópico úmido - Lins, Dandara Luiza de Mendonça Sarmento (2018)
Throughout the history of housing in Brazil, the balcony appears in several examples of the different architectural styles consolidated in the country, remaining until the present time. Despite its various functions, in this paper, the balcony is seen as an architectural element with the potential to collaborate with the environmental comfort and energy performance of buildings in the tropics. This dissertation aims to evaluate the influence of the balcony in the use of natural light in multi-family vertical residential buildings in Maceio/AL, with two specific objectives, being: a) to evaluate the interference of typologies of balustrade in the internal environment; and b) analyze the influence of incorporating the balcony into the internal environment. For the methodology, was defined a standard internal environment, while, for the balustrade, were considered the following variables: 1) depth, being: 1,05m, 1,65m, and 2,25m; 2) the reflectance of the walls, with values of 85%, 45% and 5%; 3) the type of balustrade, which may be glass and masonry; and 4) the type of use, being customary or incorporated. These variables resulted in 30 models that were simulated in the TropLux software. The simulations were performed for the east and north orientations, considering the interval from 8:30 am to 5:30 p.m. for all days of the year. The results obtained as the first specific objective, shows, as expected, that the Average Illuminance in the models with glass sill the result was always higher, reaching a variation of 12,6% to 37,8% for the east and from 14,1% to 38,6% to the north. The Uniformity results showed that the models with glass balustrade achieved the lowest results, without significant variations in the internal environment. Furthermore, the depth of the balcony caused greater variations compared to those obtained by changes in the reflectance of its inner surfaces. This study demonstrated that in the models studied, all variables considered resulted in significant changes in most cases. Thus, when designing a balcony, it is essential to know how to define its characteristics, combining the need to take advantage of natural lighting appropriately with the other conditions of the project. It was concluded, for the second specific objective, that the incorporation of the balcony resulted in inverse behaviors between the Annual Average Illuminance and Uniformity, that is, the incorporated use had lower results of the Average and Annual Average Illuminations of Uniformity than general use. Lastly, faced with this situation, the architect or user needs to consider which are the uses of the environment, considering the type of activity that will be exercised inside to choose the best configuration of a balcony.